Challenges In The Implementation Of The Family Learning Centre (Puspaga) Programme In Tambak Wedi Urban Village In The Frame Of Evidence-Based Policy - Natus, Angelique Salsabillah Yumna Patricia; Oktarizka Reviandani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The current rise in cases of domestic violence poses a serious challenge to the Surabaya City Government. One of the steps that must be taken is to formulate and implement a policy in the context of prevention and resolution. This research aims to analyze the challenges in implementing the PUSPAGA program within an evidence-based policy frame. This research uses qualitative methods with a descriptive type and interactive model analysis techniques from Miles and Huberman. Research in policy making tends to be ignored, evidence based policy has not been able to make the program achieve the envisioned goals and still needs improvement in the steps in making it, Pew MachArthur has prepared a working framework in the form of 5 backup components to make evidence based policy. As an improvement, researchers suggest optimizing the programs created by the government and conducting research for improvements in order to achieve the goal of improving the welfare of society.